Technology Entrepreneurship Project (ENT 600) : Sony Group Corporation / Akmal Haziq Ahmad Aizam - Ahmad Aizam, Akmal Haziq (2022)
A case study aims to examine an event or issue that involves a real or hypothetical situation to show how the dynamics of real-life affect decisions. Sony Corporation is the company that I selected, and the product that I concentrated on was the recently released gaming console, Play Station 5 (PS5). Gaming is a wholesome experience that people love, and as the world becomes more technologically advanced, people continue to get the most out of it. PS5 had proved to be the starting point for the future of gaming as it contains powerful hardware that provides a realistic gaming experience. After it was released, people started giving feedback and thoughts after months of using it. Despite the incredible gaming experience provided by the PS5, Sony is still plagued by several issues. People complained about the limited storage size and the problems they faced with the Dual Sense controller. The controller seems to have technical issues where it works without command, which bothers the gameplay. This case study made some suggestions for how to modify and improve the product so that customers are more pleased with it. Some of it is to allow storage expansion, whether internally or externally, and to fix the Dual Sense controller’s software and hardware problems. Sony could easily gain market share by resolving this problem, as the PS5 has a lot of promises in the future of gaming.